Linking F-box protein 7 and parkin to neuronal degeneration in Parkinson's disease (PD). Issue 1 (December 2016) - Zhou, Zhi; Sathiyamoorthy, Sushmitha; Angeles, Dario; Tan, Eng
Abstract Mutations of F-box protein 7 (FBXO7) and Parkin, two proteins in ubiquitin-proteasome system (UPS), are both implicated in pathogenesis of dopamine (DA) neuron degeneration in Parkinson's disease (PD). Parkin is a HECT/RING hybrid ligase that physically receives ubiquitin on its catalytic centre and passes ubiquitin onto its substrates, whereas FBXO7 is an adaptor protein in Skp-Cullin-F-box (SCF) SCFFBXO7 ubiquitin E3 ligase complex to recognize substrates and mediate substrates ubiquitination by SCFFBXO7 E3 ligase. Here, we discuss the overlapping pathophysiologic mechanisms and clinical features linking Parkin and FBXO7 with autosomal recessive PD. Both proteins play an important role in neuroprotective mitophagy to clear away impaired mitochondria. Parkin can be recruited to impaired mitochondria whereas cellular stress can promote FBXO7 mitochondrial translocation. PD-linked FBXO7 can recruit Parkin into damaged mitochondria and facilitate its aggregation. WT FBXO7, but not PD-linked FBXO7 mutants can rescue DA neuron degeneration in Parkin nullDrosophila . A better understanding of the common pathophysiologic mechanisms of these two proteins could unravel specific pathways for targeted therapy in PD.